Clinical and Laboratory Features Distinguishing Juvenile Polymyositis and Muscular Dystrophy. Issue 12 (December 2013) - Mamyrova, Gulnara; Katz, James D.; Jones, Robert V.; Targoff, Ira N.; Lachenbruch, Peter A.; Jones, Olcay Y.; Miller, Frederick W.; Rider, Lisa G.; ,
<x xml:space="preserve">Abstract</x> Objective To differentiate juvenile polymyositis (PM) and muscular dystrophy, both of which may present with chronic muscle weakness and inflammation. Methods We studied 39 patients with probable or definite juvenile PM and 9 patients with muscular dystrophies who were initially misdiagnosed as having juvenile PM. Differences in demographic, clinical, and laboratory results; outcomes; and treatment responses were evaluated by Fisher's exact and rank sum tests. Random forests classification analysis and logistic regression were performed to examine significant differences in multivariable models. Results Clinical features and serum muscle enzyme levels were similar between juvenile PM and dystrophy patients, except 89% of dystrophy patients had muscle atrophy compared with 46% of juvenile PM patients. Dystrophy patients had a longer delay to diagnosis (median 12 versus 4 months) and were less frequently hospitalized than juvenile PM patients (22% versus 74%). No dystrophy patients, but 54% of juvenile PM patients, had a myositis autoantibody. Dystrophy patients more frequently had myopathic features on muscle biopsy, including diffuse variation of myofiber size, fiber hypertrophy, and myofiber fibrosis (44–100% versus 8–53%). Juvenile PM patients more frequently had complex repetitive discharges on electromyography and a complete response to treatment with prednisone or other immunosuppressive agents than dystrophy patients (44% versus 0%). Random forests analysis revealed that the most important features in distinguishing juvenile PM from dystrophies were myositis autoantibodies, clinical muscle atrophy, and myofiber size variation on biopsy. Logistic regression confirmed muscle atrophy, myofiber fibrosis, and hospitalization as significant predictors. Conclusion Muscular dystrophy can present similarly to juvenile PM. Selected clinical and laboratory features are helpful in combination in distinguishing these conditions.